Design of a Low Voltage Class AB Variable Gain Amplifier (VGA) - Idris, M. Idzdihar; Zainudin, M. N. A; Ismail , M. Muzafar; Abd. Rahim, Rosman (UTEM, 2012)
A variable gain amplifier (VGA) is one of the most significant component in many applications such as analog to digital converter (ADC). In communication receiver, VGA is typically employed in a feedback loop to realize an automatic gain control (AGC), to provide constant signal power to baseband analog-to-digital converter (ADC) for unpredictable received signal strengths. Gain range, power consumption and bandwidth of ADC are strongly influenced by the performance of operational amplifier. VGA is the key element for amplifying process in ADC. However, current class AB VGA is experiencing the limit of bandwidth, which is not suitable for high speed automatic gain control AGC. In order to overcome these limitations a high linearity and wide bandwidth of VGA is indispensable. The aim of this research is to get higher gain and larger bandwidth for VGA. In this research, a low cost, low power voltage and wide bandwidth class AB VGA is designed to mitigate this constraint. Superiority of the proposed VGA has been confirmed by circuit simulation using CEDEC 0.18-μm CMOS process with the help of tools from Mentor Graphics in designing a 100-MHz VGA under 1V supply voltage draining total static power consumption less than 125uW. The results show that the circuit is able to work with high linearity and wide bandwidth by varying Rf and Rs. Therefore, the frequency response (Gain) and the wide bandwidth of this class AB VGA is better than previously reported class AB VGA. Consequently, this modified class AB VGA is appropriate for high speed applications.